PENINGKATAN EDUKASI EKONOMI KREATIF MELALUI PENGOLAHAN KRIPIK “PISITAKE” DI DESA RACEK KECAMATAN TIRIS KABUPATEN PROBOLINGGO. - Q, Nanang; Muni, Abd (Lembaga Penerbitan, Penelitian, dan Pengabdian Masyarakat (LP3M) UNZAHLP3M, 2021)
Abstract The assistance provided is to utilize local raw materials that do not have a high selling value, such as bananas, cassava, cassava and taro. Assistance is carried out starting from the selection of raw materials until the production process is complete to marketing. The processing results become chips and can add economic value to the surrounding community. The purpose of this community service is to provide knowledge to the community about entrepreneurship how to process local raw materials